Modellgestützte Optimierung eines Ultraschall-Torsionsschweißsystems - Dohmen, Markus Daniel; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias; Sextro, Walter (PLUS-Elektronikfertigung)

A comprehensive numerical study of the wetting behavior in structured packings with a direct consideration of the packing microstructure - Dechert, Christopher; Riese, Julia; Kenig, Eugeny (Chemical Engineering Science)

Steuersicherheit als Standortfaktor: Planbarkeit statt Investitionshemmnis - Sureth, Caren (Betriebs-Berater)

Verstehen adressieren und Darstellungen vernetzen: Exemplarische Aufgaben zur analytischen Geometrie - Herrmann, Janine; Hoffmann, Max; Wessel, Lena (Mathematikabitur „Status Quo – Quo Vadis“: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)
Keywords: Verstehensorientierung; Darstellungsvernetzung; analytische Geometrie; Abitur; Aufgabenentwicklung; Lehrkräfteprofessionalisierung

Different Pathways, Shared Challenges: Reflections on Entering Vocational Teaching in Germany - Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin
Germany is experiencing a shortage of teachers, a situation that is particularly evident in the domain of technical vocational education. In response to this, various pathways into vocational teacher education have been established. These pathways are diverse in their nature but all lead to the same teacher degree as traditional teacher education. In two interview studies (n=22 (pre service) vocational teachers), initial motives of entering teacher education (based on FIT-Choice) as well as retrospective views on the career choice after entering the profession (based on PLP model) are analyzed. The present study compares the reflective views of pre-service teachers and career-changing in-service teachers (CCIT). Although both groups generally perceive their career choice positively, the results raise questions about why CCITs did not enter the field of teacher education in the first place. Additionally, the analysis allows for further discussion about existing teacher education programs in times of teacher shortage.
Keywords: vocational teacher education; teacher shortage; career-changing teachers; teacher reflections

Zwischen konstitutioneller Dreisprachigkeit und realer Vielsprachigkeit: Die multilinguale Diversität in Luxemburg - Liechty, Vincent
Luxemburg gilt als Musterbeispiel für sprachliche Vielfalt: Die drei Amtssprachen Luxemburgisch, Französisch und Deutsch treffen migrations- und globalisierungsbedingt auf zahlreiche weitere Sprachen wie Portugiesisch und Italienisch. Der Artikel beleuchtet historische Entwicklungen, Sprachenpolitik und Alltagspraxis sowie Chancen wie Herausforderungen der mehrsprachigen Diversität in Luxemburg.

Shifting Minds or Reinforcing Myths? Empirical Insights into AI-related Affective Changes Among Future Technology Teachers - Vernholz, Mats; Schäfers, Johannes; Jonas-Ahrend, Gabriela; Temmen, Katrin

Exploring (De)Motivating Factors over Time: Perspectives of Career Change STEM Teachers from Germany and Israel - Guberman, Ainat; Jonas-Ahrend, Gabriela; Arvif-Elyashiv, Rinat; Ben-Yehduah, Gal; Cyprus, Dominik

The True Story Of A Total Fake. Eine Untersuchung des didaktischen Potenzials der Hochstaplerin Anna Delvey in der Miniserie Inventing Anna - Intveen, Julie (Hochstapelei in der Gegenwartskultur. Literaturwissenschaftliche und literaturdidaktische Perspektiven)
Figuren der Hochstapelei faszinieren als Meister:innen der Verstellung. Ob in Literatur, Film oder Realität – sie inszenieren sich virtuos und entlarven die Oberflächlichkeit einer Gesellschaft, die sich von Äußerlichkeiten blenden lässt. Sie stellen soziale Grenzen infrage und verkörpern einen subversiven Geist, der den Wunsch nach Ausbruch widerspiegelt. Doch was poetisch bewundert wird, ist real oft justiziabel und hat zerstörerische Folgen für die Betrogenen. Dieser Band nähert sich der Hochstapelei als kultureller Praxis der Gegenwart. Welche gesellschaftlichen, kulturellen und medialen Bedingungen begünstigen das Hochstapeln? Und was bedeutet es für die Identitätsarbeit in der Moderne, wenn die Grenzen zwischen Sein und Schein verschwimmen? Anknüpfend an bisherige Forschungsdiskussionen versammeln die literaturwissenschaftlichen und literaturdidaktischen Beiträge Antworten auf diese Fragen. Darüber hinaus beleuchten sie die enge Verknüpfung von Fiktion, Täuschung und Selbstinszenierung.

Praxisforschung in Schule und Unterricht - Textor, Annette; Kullmann, Harry; van der Donk, Cyrilla; van Lanen, Bas
Für Lehrer*innen ist es wichtig, über die Qualität ihrer Arbeit informiert zu sein, um sich an Schul- und Unterrichtsentwicklung beteiligen zu können. Das vorliegende Lehrbuch bietet anhand eines erprobten Modells – eines Forschungszyklus in Verbindung mit einem ergänzenden Innovationszyklus – konkrete Hilfestellungen, um die eigene Tätigkeit zu reflektieren und weiterzuentwickeln. Der zugrundeliegende Ansatz verbindet erfolgreiche Verfahren aus der niederländischen Lehrerinnen- und Lehrerbildung mit etablierten Methoden der schulischen Praxisforschung im deutschsprachigen Raum. Zahlreiche alltagsbezogene Beispiele illustrieren die Grundsätze und Verfahrensschritte, während Übungsaufgaben zu Vertiefung und Wiederholung anregen.
Keywords: Praxisforschung; Schulentwicklung; Inklusion; Data Literacy

‘School is no longer a lone wolf effort’: leadership strategies for inclusive, community-based school cultures - Kullmann, Harry; Kullmann, Harry; Kullmann, Harry; Kullmann, Harry; Kullmann, Harry; Kullmann, Harry; Kullmann, Harry; Kullmann, Harry; Kullmann, Harry (School Leadership & Management)

Studie der Uni Paderborn: Ausbildung mit System – Wenn Schule und Betrieb an einem Strang ziehen - Schwede, Jana; Zidi, Christel; Sommer, Sonja; Schneider, Lena; Butz, Sabina (Elternratgeber im sauerland)

Documenting Britishness in Decline: Spatial Representations of a Fragmented Nation in Paul Graham’s Photobook A1 - Tönnies, Merle (Welcome to Retrotopia: Placing Visions of ‘Britishness’ in the Long Twentieth Century)

In-situ CT of Viscoelastic Plastic Materials: A Radiography-Based Lead Time Determination for Composite–Metal Joints at Elevated Temperature - Dargel, Alrik; Troschitz, Juliane; Gude, Maik; Kupfer, Robert (e-Journal of Nondestructive Testing)
In-situ computed tomography (CT) experiments on materials with time-dependent mechanical behaviour are affected by relaxationinduced motion, which can lead to image blur and motion-related artefacts if scans are initiated before relaxation-induced motion has subsided. Scan start times are therefore commonly defined based on force relaxation or force-gradient criteria, although these signals do not directly quantify image-relevant specimen motion. In this work, a radiography-based approach is presented to estimate relaxation-induced motion via pixel shifts from projection images acquired prior to CT scans. These projection-based pixel shift estimates of relaxation-induced motion are related to scan-specific image blur observed in the reconstructed volumes. Thereby, a direct link between specimen motion during the scan and CT image quality is established. The method is demonstrated for thermo-mechanically loaded specimens with pronounced temperature-dependent material behaviour, where relaxation-induced motion persists over extended time scales. The results show that projection-based pixel shift estimation provides a physically meaningful and experimentally accessible basis for defining scan start criteria. CT acquisition can be initiated based on an allowable level of relaxation-induced motion, rather than waiting for mechanical equilibrium to be reached. The proposed approach therefore offers a direct, image-related framework for scan timing in in-situ CT experiments on time-dependent materials.

U. Niggemann (Hg.): Der Bauernkrieg von 1525. Staatlichkeit und Ordnungsvorstellungen (= Staatsverständnisse. 185). Baden-Baden 2025 - Moritz, Tilman (sehepunkte)

Application of Novel Exponential (Semi-)Parametric Short and Long Memory GARCH Models under Regulatory Requirements of Basel III - Hanke, Dominik Christian; Uhde, André; Feng, Yuanhua
This paper evaluates the forecasting performance of an expanded class of (semi-)parametric GARCH models belonging to the EGARCH family (EGF), including recently introduced long and short memory specifications and their semiparametric extensions. The semiparametric variants employ a multiplicative volatility decomposition into conditional and slowly varying unconditional components, where the latter is estimated via a data-driven local polynomial smoother to accommodate non-stationarities commonly observed in financial time series. Based on the revised Basel Committee framework for market-risk assessment, all models are capable of producing rolling one-day-ahead forecasts for Value at Risk (VaR) and Expected Shortfall (ES) under a wide range of symmetric and skewed innovation distributions. Their forecasting accuracy is examined using the regulatory traffic light tests for VaR and the recently developed ES-specific traffic light procedure, complemented by the regulatory loss function. In addition, model selection incorporates both a recently proposed corrected firm-oriented loss function that accounts for opportunity costs and the Weighted Absolute Deviation (WAD) criterion. The empirical comparison demonstrates that (semiparametric) long memory GARCH models - particularly those combining fractional dynamics with nonparametric scale adjustments - can serve as valuable alternatives to traditional parametric short memory models, offering more stable volatility estimates and improved tail-risk forecasts for practical risk management applications.
Keywords: semiparametric GARCH extension; data-driven local polynomial smoother; long memory; GARCH models; Value at Risk; Expected Shortfall; traffic light test; backtesting; Basel III; market risk

Comparing the behaviors of some original short and long memory exponential volatility models - Hanke, Dominik Christian; Feng, Yuanhua; Uhde, André
Volatility modeling is utilized across numerous fields including finance, environmental studies, and social sciences. It is particularly relevant in scenarios where understanding and predicting conditional variability is crucial, such as when dealing with incremental or time-dependent data. In this paper, novel short and long memory volatility models of the EGARCH family are introduced and analyzed, which are closely related to the well-established EGARCH model proposed by Nelson (1991) but share desirable theoretical properties in several dimensions. Recently developed members of the so-called EGARCH family, which introduces a modulus-log transformation proposed by John and Draper (1980) and a power transformation for the size and magnitude effect to tackle the problem with near-zero innovations and the asymmetric impact of positive and negative shocks on the volatility, are discussed. After a theoretical discussion of the proposed and related volatility models, the practical performance of the elaborated volatility models is compared to well-established and traditional GARCH approaches. A general QMLE algorithm is proposed to estimate the model parameters. The practical relevance of the advanced models is illustrated through a comparative study. By applying these volatility models to a variety of international stock index returns, this paper identifies market-specific characteristics as well as unique strengths and weaknesses of discussed volatility models. Although the practical performance of the recently introduced models is comparable to those obtained by the traditional EGARCH model, they generally outperform traditional non-exponential volatility models used as benchmarks and thus provide a useful alternative to existing short and long memory volatility models.
Keywords: Modulus Log-GARCH; Modified (FI)EGARCH; Modulus asymmetric (FI)Log-GARCH; (FI)EGARCH; long memory; modulus-log transformation; QMLE; model selection; implementation in R

Unterstützung von Verstehen im Fachunterricht. Eine Grounded Theory zum sprach- und fachverbindenden Geschichtsunterricht - Müller, Jennifer
Wie verläuft der Leseprozess im Geschichtsunterricht für Schüler:innen, die neu in das deutsche Bildungssystem einsteigen – und welche Faktoren beeinflussen ihr Verstehen? Diese Studie untersucht an der Schnittstelle von Deutsch als Zweitsprache und Geschichtsdidaktik die Bedingungen des Lesens im Geschichtsunterricht. Im Fokus stehen die Erfahrungen von Seiteneinsteiger:innen sowie die Perspektiven der Lehrkräfte, die im Rahmen einer qualitativ‑explorativen Untersuchung mithilfe von Unterrichtshospitationen, Interviews und Materialanalysen erhoben wurden. Methodisch ist die Arbeit in der Grounded Theory Methodology nach Strauss und Corbin (1996) verankert, anhand derer die komplexen Einflussfaktoren historischer Leseprozesse systematisch herausgearbeitet werden. Die Ergebnisse zeigen drei zentrale Einflussdimensionen: sprachliche, sozial‑affektive und geschichtsspezifische Faktoren. Zudem wird deutlich, dass Unterstützungsmaßnahmen stets zwischen kurzfristiger Hilfe und dem langfristigen Aufbau von Disciplinary Literacy ausbalanciert werden müssen. Ihre Wirksamkeit hängt wesentlich von der bewussten Auswahl und Zugänglichkeit durch die Lehrkraft sowie von den Möglichkeiten der Lernenden ab, Unterstützung gezielt einzufordern. Lernwirksam wird Geschichtsunterricht besonders dann, wenn hohe fachliche Anforderungen mit reflektierter sprachlicher Unterstützung verbunden werden. Die Studie leistet damit einen Beitrag zur Forschung zu sprachbewusstem Fachunterricht und bietet Impulse für eine kritisch‑reflexive Sprachsensibilität in schulischen Bildungsprozessen.
Keywords: Scaffolding; Sprache und Fach; Grounded Theory Methodology; Lesen in der Sekundarstufe I; Sprachsensibler Geschichtsunterricht; Durchgängige Sprachbildung

Metallopolymers via thermal dealkylation of unstrained bisphosphanylferrocene precursors - Dey, Subhayan; Szathmári, Balázs; Langgut, Dennis; Gutmann, Torsten; Kelemen, Zsolt; Pietschnig, Rudolf (Journal of Materials Chemistry A)
Metallopolymers with 1D phosphorus chains are accessible from simple unstrained precursors and feature a narrow band gap associated with red-shifted absorption in the UV-vis range.

Diplomatic Transcriptions Between Document and Text: Encoding Beethoven’s Sketchbooks - Kepper, Johannes (Transactions of the International Society for Music Information Retrieval)